Longitudinal Measurement Invariance of Posttraumatic Stress Disorder in Deployed Marines. Issue 3 (4th May 2017) - Contractor, Ateka A.; Bolton, Elisa; Gallagher, Matthew W.; Rhodes, Charla; Nash, William P.; Litz, Brett
Abstract : The meaningful interpretation of longitudinal study findings requires temporal stability of the constructs assessed (i.e., measurement invariance). We sought to examine measurement invariance of the construct of posttraumatic stress disorder (PTSD) as based on the Diagnostic and Statistical Manual of Mental Disorders indexed by the PTSD Checklist (PCL) and the Clinician‐Administered PTSD Scale (CAPS) in a sample of 834 Marines with significant combat experience. PTSD was assessed 1‐month predeployment (T0), and again at 1‐month (T1), 5‐months (T2), and 8‐months postdeployment (T3). We tested configural (pattern of item/parcel loadings), metric (item/parcel loadings on latent factors), and scalar (item/parcel‐level severity) invariance and explored sources of measurement instability (partial invariance testing). The T0 best‐fitting emotional numbing model factor structure informed the conceptualization of PTSD's latent factors and parcel formations. We found (1) scalar noninvariance for the construct of PTSD as measured by the PCL and the CAPS, and for PTSD symptom clusters as assessed by the CAPS; and (2) metric noninvariance for PTSD symptom clusters as measured by the PCL. Exploratory analyses revealed factor‐loading and intercept differences from pre‐ to postdeployment for avoidance symptoms, numbing symptoms (mainly psychogenic amnesia and foreshortened future), and the item assessing startle, each of which reduced construct stability. Implications of these findings for longitudinal studies of PTSD are discussed.